Penology the keepers of the keys - The Open University BBC TV; Hobel-Leiterman Productions ([United Kingdom] : The Open University, 1971)
Demonstrates what criminals can expect in tomorrow's society.
Converted into VHS 1/2 in. and DVD
Bahan rosak (Lupus)
Keywords: Crime; Criminals; Corrections